Observation of horizontal temperature variations by a spatial heterodyne interferometer using single-sided interferograms - K. Ntokas; J. Ungermann; M. Kaufmann; T. Neubert; M. Riese (Atmospheric Measurement Techniques, 2023)
Analyses of the mesosphere and lower thermosphere suffer from a lack of global measurements. This is problematic because this region has a complex dynamic structure, with gravity waves playing an important role. A limb-sounding spatial heterodyne interferometer (SHI) was developed to obtain atmospheric temperature retrieved from the O2 A-band emission, which can be used to derive gravity wave parameters in this region. The 2-D spatial distribution of the atmospheric scene is captured by a focal plane array. The SHI superimposes the spectral information onto the horizontal axis across the line-of-sight (LOS). In the usual case, the instrument exploits the horizontal axis to obtain spectral information and uses the vertical axis to get spatial information, i.e. temperature observations at the corresponding tangent points. This results in a finely resolved 1-D vertical atmospheric temperature profile. However, this method does not make use of the horizontal across-LOS information contained in the data.